2009
DOI: 10.1063/1.3072441
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of Co0.8MnxFe2.2−xO4 (x=0.2, 0.4, 0.6, 0.8) polycrystalline powders synthesized by sol-gel process

Abstract: Co 0.8 Mn x Fe 2.2 − x O 4 (x=0.2, 0.4, 0.6, and 0.8) powders were prepared by a sol-gel process and annealed at different temperatures (Ta=600, 800, 1000, and 1200 °C). X-ray diffractometer results reveal that all the samples are inverse-type spinel with cubic structure. The magnetic properties were measured by vibrating sample magnetometer and the results indicate that the saturated magnetization (Ms) and coercivity (Hc) decrease with increasing Mn content x. The decrease in Ms is related to the magnetic mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…CoMn 2 O 4 , and CoFe 2 O 4 ,, spinels were reported as high-capacity anode materials, but Li uptake into CoMnFeO 4 has not been investigated, yet. CoMnFeO 4 was synthesized as thin films , and as powders for determination of the cation distribution and magnetic and catalytic properties. , Here we report for the first time on the electrochemical performance of CoMnFeO 4 nanoparticles as anode material. Furthermore, we investigate the reaction mechanism during Li insertion into the quaternary spinel by operando synchrotron-based XRD and XAS allowing monitoring the individual structural and electronic events occurring during the reaction.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…CoMn 2 O 4 , and CoFe 2 O 4 ,, spinels were reported as high-capacity anode materials, but Li uptake into CoMnFeO 4 has not been investigated, yet. CoMnFeO 4 was synthesized as thin films , and as powders for determination of the cation distribution and magnetic and catalytic properties. , Here we report for the first time on the electrochemical performance of CoMnFeO 4 nanoparticles as anode material. Furthermore, we investigate the reaction mechanism during Li insertion into the quaternary spinel by operando synchrotron-based XRD and XAS allowing monitoring the individual structural and electronic events occurring during the reaction.…”
Section: Introductionmentioning
confidence: 94%
“…CoMn 2 O 4 39,40 and CoFe 2 O 4 30,31,41 spinels were reported as high-capacity anode materials, but Li uptake into CoMnFeO 4 has not been investigated, yet. CoMnFeO 4 was synthesized as thin films 42,43 and as powders for determination of the cation distribution and magnetic and catalytic properties. 44,45 Here we report for the first time on the electrochemical performance of CoMnFeO 4 nanoparticles as anode material.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt-ferrite Co x Fe 3 À x O 4 (0 rxr1) films have attracted many attentions for decades not only due to their high-electromagnetic performance and excellent chemical stability [1][2][3][4], but also high cubic magnetocrystalline anisotropy, high coercivity, and moderate saturation magnetization [5], which makes them have potential applications in commercial videos, audio tapes, highdensity digital recording media [6][7][8], and magnetic fluids [9].…”
Section: Introductionmentioning
confidence: 99%
“…Kambale et al (2010) have prepared Co 1-x Mn x Fe 2 O 4 by combustion route and reported that the lattice constant and coercivity increase with the Mn concentration whereas, the saturation magnetization initially increases, then it decrease. Lu et al (2009) have synthesized Co 0.8 Mn x Fe 2.2-x O 4 by sol gel process and showed that the saturation magnetization and coercivity decrease with increase of Mn concentration. Melikhov et al (2006) have studied the magnetic properties of CoMn x Fe 2-x O 4 and observed that saturation magnetization and cubic magnetocrystalline anisotropy decreases with the Mn concentration.…”
Section: Introductionmentioning
confidence: 99%